PENGARUH EDUKASI DENGAN MEDIA SOSIAL INSTAGRAM DAN YOUTUBE TERHADAP PENGETAHUAN DAN SIKAP GIZI LEBIH (OVERWEIGHT) PADA REMAJA DI MAN 1 KOTA BOGOR - Shafira Salzakilla Damayanti (2022)
The high prevalence of overweight in adolescents is one of the nutritional problems in Indonesia. The provision of nutrition education is a solution to increase knowledge and attitudes about overweight in adolescents by utilizing social media Instagram and YouTube, which are currently multiplying in accessing information faster. This study was conducted to determine the effect of education on social media, Instagram and YouTube on adolescents' knowledge and attitudes toward overweight. The method used in this research is quasi-experimental, with the number of respondents being 98 students in classes X and XI, which are divided into four groups, namely Instagram, YouTube, Instagram and YouTube groups and controls. The results of this study indicate an increase in knowledge and attitudes with a value (p <0.05) and differences in the effectiveness of knowledge. There is no difference in attitudes between Instagram and YouTube media. Then, there is no difference in effectiveness between Instagram and combined media (Instagram and YouTube) on knowledge and attitudes in adolescents. Furthermore, there is no difference in effectiveness between YouTube media and combined media (Instagram and YouTube) on knowledge and attitudes in adolescents.